2022
DOI: 10.2147/ppa.s352332
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Characteristics and Secondary Medication Adherence Patterns Among Patients Receiving Tafamidis Prescriptions: A Retrospective Analysis Using a National Specialty Pharmacy Dispensing Database

Abstract: Introduction Transthyretin amyloid cardiomyopathy (ATTR-CM) is a serious, underrecognized condition, which leads to heart failure and early mortality if left untreated. Until recently, heart transplantation was the only treatment for ATTR-CM. Regulatory approval of tafamidis transformed treatment for patients. In the phase 3 Transthyretin Amyloidosis Cardiomyopathy Clinical Trial (ATTR-ACT), which established the safety and efficacy of tafamidis, medication adherence was high with 97.2% of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…The current study found patient adherence rates of over 90% for both calculation methods. The mMPR was 94.6%, similar to the mMPR of 96% and 92% in a Japan and US study of patients treated with tafamidis, respectively [ 1 , 14 ]. These patient adherence rates are higher than the estimated 57% reported in a meta-analysis for other cardiovascular drugs [ 16 ].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The current study found patient adherence rates of over 90% for both calculation methods. The mMPR was 94.6%, similar to the mMPR of 96% and 92% in a Japan and US study of patients treated with tafamidis, respectively [ 1 , 14 ]. These patient adherence rates are higher than the estimated 57% reported in a meta-analysis for other cardiovascular drugs [ 16 ].…”
Section: Discussionsupporting
confidence: 80%
“…A previously conducted US Medicare real-world study on tafamidis for patients with ATTR-CM found very similar patient characteristics in the USA. In that study, the mean age was 75 years and 83.2% of the included patients were male [ 14 ]. Similarly, another claims study that analyzed ATTR-CM incidence and prevalence in France found a slightly lower proportion of male patients (66.9%) and a numerically higher mean age of 81 years at diagnosis [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specialty pharmacies serve to provide medications for conditions requiring high-cost complex therapies, monitoring, and/or special communication with patients, and provide services such as benefits verification, access to patient financial assistance programs, and assistance with prior authorization. While there is initial evidence from Medicare and specialty pharmacy databases suggesting that adherence to tafamidis transthyretin stabilizer therapy is good if it is prescribed (28,29), there is no data describing where in the clinical pathway the drop off of patient groups occurs and whether drop off was due to any identifiable patient characteristics.…”
Section: Introductionmentioning
confidence: 99%